An Adult Case of Severe Asymptomatic Bilateral Ureteropelvic Junction Obstruction - Md Fahad Hossain; Syed Sheheryar Shah; Bahar Bastani (Case Reports in Nephrology)
While ureteropelvic junction (UPJ) obstruction is a well-recognized cause of unilateral or bilateral upper urinary tract dilatation in infants and the pediatric population, its occurrence in adults is less recognized. We present the case of a 68-year-old man who was being evaluated for chronic orthostatic hypotension and was incidentally found to have asymptomatic microscopic hematuria on urinalysis. A CT scan of the abdomen/pelvis, without and with contrast, revealed severe bilateral hydronephrosis due to UPJ obstruction. The patient has remained asymptomatic with preserved normal renal function over 7 years of follow-up.